Ação antimicrobiana de gordura corporal do lagarto téju (Tupinambis merianae) - Silva, Tereza Kamilla Sousa (Universidade Federal Rural do Semi-Árido, 2019)
Téju (Tupinambis merianae) is a lizard native to South America, where it lives in forested regions, open areas and vegetation. Its fat is used as a zootherapic by several traditional communities. This fat has anti-inflammatory activity, being used in the treatment of several diseases, mainly for tonsil infections, which makes us believe that the fat has antimicrobial potential. The aim of this study was to verify the antimicrobial activity of the crude Téju fat extract (T. merianae) and compare it to the conventional antimicrobials for S. aureus, E. coli, P. aeruginosa, S. Typhimurium, K. pneumoniae, S. agalactiae, S. flexneri and a fungus classified as C. albicans. The study was conducted using well-diffusion and disk-diffusion techniques using crude fat extract and conventional antimicrobials such as amikacin, ampicillin, amoxicillin + clavulan, aztreonam, cephalothin, cefepime, ceftriaxone, cefoxitin, ceftazidime, ciprofloxacin, chloramphenicol , streptomycin, gentamycin, novobiocin, piperacillin + tazobactam, polymyxin, sulfamethoxazole + trimethoprim, vancomycin, tetracycline. The microdilution technique was also used to determine the antimicrobial potential of fat at different concentrations for the two microorganisms that showed sensitivity to the crude fat extract in the well diffusion technique. It was observed that the bacteria S. Typhimurium and P. aeruginosa had an antimicrobial resistance profile amoxicillin + clavulanic acid, ampicillin, ceftazidime, chlorafenicol, cefotixine, cefepime, piperacillin / Tazobactam, polymyxin, vancomycin, but presented a halo greater than 10 mm in the well diffusion technique when tested for sensitivity to the crude extract of T. merianae fat and the concentrations of 25 mg / ml and 50 mg / ml of fat in the microdilution technique showed action against the microorganisms in a similar way to that of positive control (gentamicin 20mg / ml), although there is no statistically significant difference. It is concluded that the crude extract of the T. merianae fat presented in both the well diffusion technique and the microdilution, the antimicrobial capacity for the S. Typhimurium and P. aeruginosa bacteria.
Monografia
Keywords: Antibacterianos; Antifúngicos; Banha; Zooterapia; Antibacterials; Antifungals; Body fat; Zootherapy; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA